Universal RNA Secondary Structure Insight Into Mosquito-Borne Flavivirus (MBFV) cis-Acting RNA Biology - Zeng, Miao; Duan, Yanping; Zhang, Wei; Wang, Mingshu; Jia, Renyong; Zhu, Dekang; Liu, Mafeng; Zhao, Xinxin; Yang, Qiao; Wu, Ying; Zhang, Shaqiu; Liu, Yunya; et al. (Frontiers in Microbiology, 2020)
Mosquito-borne flaviviruses (MBFVs) spread between vertebrate (mammals and birds) and invertebrate (mosquitoes) hosts. The cis-acting RNAs of MBFV share common evolutionary origins and contain frequent alterations, which control the balance of linear and circular genome conformations and allow effective replication. Importantly, multiple cis-acting RNAs interact with trans-acting regulatory RNA-binding proteins (RBPs) and affect the MBFV lifecycle process, including viral replicase binding, viral RNA translation-cyclisation-synthesis and nucleocapsid assembly. Considering that extensive structural probing analyses have been performed on MBFV cis-acting RNAs, herein the homologous RNA structures are online folded and consensus structures are constructed and sorted. The important MBFV cis-acting RNA traits and underlying virus biology are illuminated accordingly in a review of MBFV cis-acting RNA structure.